High resolution mass spectrometry analysis of the sertraline residues contained in the tissues of rainbow trout reared in model experimental conditions - Vaclavik, J; Senohova, P; Medkova, D; Stastny, K; Charvatova, M; Faldyna, M; Mares, J; Svobodova, Z (Physiological research, 2020)
The growing consumption of pharmaceuticals in the human population and the insufficient efficiency of their elimination in waste water has a long-term negative impact on the environment of aquatic ecosystems, including the organisms that inhabit them. A significant contributor is the consumption of anti-depressants from the SSRI group, which corresponds to their increasing concentration in the environment. The aim of this work was to determine if antidepressant sertraline is able to be stored in fish organisms and to evaluate the content of residues in various body tissues. Rainbow trout (Oncorhynchuss mykkis) was selected as the test organism and was artificially exposed to the antidepressant for 1 month (concentrations 0; 4.2; 44 and 400 ng.g-1 sertraline in the feed). Liver, kidney, brain and muscle tissue biopsies samples were taken for analysis. Detection was performed using an Accela 1250 LC pump and an Accela autosampler coupled with a high-performance mass analyzer with a heated electrospray ionization source Q-Exactive Orbitrap, operating in positive ionization mode and in PRM mode (m/z 306.08108->275.03888 and 309.009991->275.03888 for sertraline and internal standard, respectively). The limit of quantification of the method was 0.1 ng.g-1 of sertraline and the calibration curve showed a good linearity up to 20 ng.g-1. From the collected data, amount of residues was found in the liver, kidney and brain. In contrast, the incidence of residues in muscle tissue was not detected in all groups, which is favorable from the point of view of fish meat consumption, by humans.
Keywords: Selective Serotonin Reuptake Inhibitors; Sertraline; obsah radioaktivních látek v organizmu; rezidua léčiv; sertralin; Water Pollutants, Chemical; Tandem Mass Spectrometry; Animals; Serotonin Uptake Inhibitors; hmotnostní spektrometrie s elektrosprejovou ionizací; Oncorhynchus mykiss; zvířata; Spectrometry, Mass, Electrospray Ionization; tkáňová distribuce; tandemová hmotnostní spektrometrie; Body Burden; selektivní inhibitory zpětného vychytávání serotoninu; chemické látky znečišťující vodu; Drug Residues; Tissue Distribution